Alzheimer’s Type Neuropathological Changes in a Patient with Depression and Anxiety: A Case Report and Literature Review of Neuropathological Correlates of Neuropsychiatric Symptoms in Alzheimer’s Disease - Sumit Das (Case Reports in Neurological Medicine)
Alzheimer’s disease (AD) is classified as a tauopathy and is the most common neuropathological correlate of dementia/cognitive impairment. AD is neuropathologically characterized by the presence of beta-amyloid immunoreactive senile plaques and tau positive neurofibrillary tangles. Neuropsychiatric symptoms of AD however continue to be underscored, and therefore, neuropathological correlates of these neuropsychiatric symptoms are not readily studied. Presented here is a case of 60-year-old female who initially presented with anxiety and depression, and continued to be the predominant symptoms although mild cognitive impairment was noted as per the available clinical notes. Postmortem examination of the brain revealed severe Alzheimer’s type neuropathological changes, which included significant tau and beta-amyloid pathology in limbic regions, which were thought to represent correlates of the patient’s depression and anxiety. This case report illustrates the possible neuropathological correlates of neuropsychiatric symptoms in patients with AD. The author hopes that such a case will promote more in-depth studies into the pathophysiology of neuropsychiatric manifestations in AD.